Mexico : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2021)
This Report on the Observance of Standards and Codes-Data Module (Data ROSC) updates assessments conducted in 2010 and 2015. The updated assessments are based on the May 2012 version of the IMF's Data Quality Assessment Framework (DQAF) and cover the national accounts, government finance, and external sector statistics. The National Institute of Statistics and Geography (INEGI) is responsible for the national accounts, the Secretariat of Finance and Public Credit (SHCP) for the government finance statistics (except for data on state and local governments, which are the responsibility of INEGI), and the Bank of Mexico (BM) for the external sector statistics.